Project-Based Learning Assisted with Mind Mapping on Description Essay Writing Skills : A Study in Elementary School - Nanda Anisa Faturohmah; Apri Irianto; Reza Rachmadtullah (Journal of Education and Teacher Training Innovation, 2023)
Writing essays with a descriptive structure is one of the basic competencies. A descriptive essay is a true depiction of objects or events so that the reader feels what the writer feels in the story. However, the level of students' ability to write descriptive essays is still low given the lack of understanding in writing descriptions so it is difficult to find ideas to translate into written form, and the choice of vocabulary is not quite right in constructing sentences. Therefore, this study aims to determine whether there is an influence of the project-based learning model assisted by mind mapping on students' descriptive essay writing skills. The method of this research is Quasi Experiment with a pretest-posttest control group design. Quasi experiment was conducted to determine the effect of a treatment on the subject under study. The research subjects were 50 students of class fourth-grade at Dukuh Menanggal I/424 Public Elementary School, Surabaya. Data analysis techniques using normality test, homogeneity test, and hypothesis testing. The results showed that there was an influence of the Mind Mapping-assisted Project Based Learning learning model on literacy skills in writing essay descriptions of grade IV students. In addition, with the help of Mind Mapping, can students learn motivation in writing descriptive essays because it helps focus students' minds in composing sentences into paragraphs.